2004
DOI: 10.1002/pros.20081
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosulindac (NCX 1102): A new nitric oxide‐donating non‐steroidal anti‐inflammatory drug (NO‐NSAID), inhibits proliferation and induces apoptosis in human prostatic epithelial cell lines

Abstract: Our results demonstrate the anti-proliferative and proapoptotic activity of nitrosulindac on prostate cancer cell lines and suggest its potential interest for new strategies in the management of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Similar results have recently been found culturing prostate carcinoma cells in the presence of NO-donating non-steroidal anti-inflammatory drugs like nitrosulindac, NO-ibuprofen or NO-aspirin, which, after enzymatic cleavage release NO intracellularly. Using these compounds the AR-positive cell line LNCaP was found to be considerably more sensitive than AR-negative prostate cell lines like PC3 (Huguenin et al, 2004), although this phenomenon appeared to be time-dependent (Royle et al, 2004). Neoplastic tissue may be considered as a Darwinian microenvironment, where inflammatory products and/or growth factors select for tumor cells, which are able to proliferate signal independently.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have recently been found culturing prostate carcinoma cells in the presence of NO-donating non-steroidal anti-inflammatory drugs like nitrosulindac, NO-ibuprofen or NO-aspirin, which, after enzymatic cleavage release NO intracellularly. Using these compounds the AR-positive cell line LNCaP was found to be considerably more sensitive than AR-negative prostate cell lines like PC3 (Huguenin et al, 2004), although this phenomenon appeared to be time-dependent (Royle et al, 2004). Neoplastic tissue may be considered as a Darwinian microenvironment, where inflammatory products and/or growth factors select for tumor cells, which are able to proliferate signal independently.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using NO-sulindac demonstrated a cytotoxic and antiproliferative effect on normoxic LNCaP and PC-3 cell lines. 35,36 In these previous studies by Huguenin et al, 36 NO-sulindac was also found to alter the cell cycle, induce mitotic arrest and display pro-apoptotic activity in malignant and benign cell lines. The results of the normoxia experiments in the present study concur with these previous results showing a reduction in PC-3 cell viability in a dose-and time-dependent manner following treatment with NO-sulindac as well as a comparable rate of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors observed that NO inhibited proliferation and had proapoptotic effects on the epithelial cells of the prostate (15,22).…”
Section: Discussionmentioning
confidence: 92%
“…Various exogenous precursors of nitric oxide were used in the studies on the effects of NO on various tissues and organs in experimental animals, as well as humans (15), including non-steroidal anti-inflammatory drugs (NSAID), (22) so-called donors of nitric oxide (NO-NSAID) (15): NO-inbuprofen (NCX 2111), NOaspirin (NCX 4060) (22), and nitrosulindac (NCX 1102) (15). Other precursors of exogenous nitric oxide also included: sodium nitroprusside (SNP) (2), and S-nitroso-N-acethyl-penicylamine (SNAP) (19).…”
Section: Discussionmentioning
confidence: 99%